2020
DOI: 10.1089/ast.2018.1964
|View full text |Cite
|
Sign up to set email alerts
|

The Limits, Capabilities, and Potential for Life Detection with MinION Sequencing in a Paleochannel Mars Analog

Abstract: No instrument capable of direct life detection has been included on a mission payload to Mars since NASA's Viking missions in the 1970s. This prevents us from discovering if life is or ever was present on Mars. DNA is an ideal target biosignature since it is unambiguous, nonspecific, and readily detectable with nanopore sequencing. Here, we present a proof-of-concept utilization of the Oxford Nanopore Technologies (ONT) MinION sequencer for direct life detection and show how it can complement results from esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 101 publications
(155 reference statements)
0
11
0
Order By: Relevance
“…This miniaturized technology was used for the first time in 2016 in the frame of Biomolecule Sequencer project [67,68] with the aim to detect unambiguous signs of life through nucleic acids sequencing, starting from a small amount of sample. The advantage of the in situ DNA detection with a miniaturized tool also allows minimizing any eventual contamination from terrestrial microorganisms [69]. Accordingly, our results suggested that, in spite of the treatments, the nucleic acids are still detectable by qPCR technique.…”
Section: Discussionmentioning
confidence: 63%
“…This miniaturized technology was used for the first time in 2016 in the frame of Biomolecule Sequencer project [67,68] with the aim to detect unambiguous signs of life through nucleic acids sequencing, starting from a small amount of sample. The advantage of the in situ DNA detection with a miniaturized tool also allows minimizing any eventual contamination from terrestrial microorganisms [69]. Accordingly, our results suggested that, in spite of the treatments, the nucleic acids are still detectable by qPCR technique.…”
Section: Discussionmentioning
confidence: 63%
“…Since the Viking missions in the 1970s, nucleic acid detection instruments have not been included onboard life-detection rovers; however, the miniaturization of PCR devices could allow their integration in future missions. Indeed, the development of, e.g., the MinION device (Oxford Nanopore Technologies), a portable nanopore real-time sequencer that requires just small DNA or RNA amounts, would enable the clear detection of signs of life [72].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in quality generated by the addition of MinION sequences to HiSeq datasets also demonstrates the utility of hybrid assembly in astrobiology and biosignature detection studies; post-initial DNA detection with the MinION, sample return and lab sequencing increase the information yielded to better characterize the natural consortia in extreme environments and elucidate further ways to detect them based on their genomes. MinION sequencing has strong potential for biosignature detection in future robotic and human planetary science missions based on its very small size/mass, minimal power requirements, and ability to produce reliable sequences from extreme environments 12 , 17 , 18 . Nucleic acids are complex organic polymers that can only be produced by living systems, thereby providing an unequivocal biosignature; coupled with a reliable database, the MinION could readily determine if DNA/RNA sequences produced are terrestrial contaminants 104 , enabling a measure of protection against forward contamination in space missions and theoretically straightforward determination of non-terrestrial sequences (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although considerable challenges remain in developing this technology for robotic space missions (e.g. automation of nucleic acid extraction and sequencing preparation, development of non-degrading solid state nanopores) 18 , the MinION’s proven functionality in microgravity and space conditions 17 , 19 , 20 , 105 indicate its suitability for future life detection missions. While we have shown that MinION sequences can be used to supplement and improve HiSeq data to produce superior MAGs 39 , we have also demonstrated that the high sequencing error rate inherent in MinION technology currently precludes obtaining high-quality MinION-only MAGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation